Claude Lévi-Strauss’s category of time - Ocieczek, Wioletta (Folia Philosophica, 2000)
Of foremost importance for Lévi-Strauss is his distinction, coming from Saussure, into langue (which belongs to the domain of the reversible time) and parole, i.e. individual speech (pertaining to the zone of the irreversible time). He divides scientific research into synchronic, or placed outside time, and diachronic, that is placed within time, or, in other words, historical. An important notion for him is structure, which is non-temporal, placed outside our consciousness. The concept of myth, in his philosophy, refers to a kind of narrative in which everything may happen. It is defined as a certain temporal system who has the features of reversible and irreversible time.